2016
DOI: 10.18632/oncotarget.7699
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor inflammation in gross tumor volume as a prognostic factor for nasopharyngeal carcinoma patients

Abstract: PurposeThe objective of this study is to investigate the prognostic value of primary tumor inflammation (PTI) in nasopharyngeal carcinoma (NPC) in the era of intensity-modulated radiation therapy (IMRT).ResultsPTI was observed in 376/1708 (22.0%) patients, and was present in the sphenoid sinus in 289/376 (76.9%), in the nasal cavity in 27 (7.2%), and in both places in 60 (15.9%). The estimated 4-year local relapse-free survival (LRFS), disease-free survival (DFS), overall survival (OS) and distant metastasis-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As early as 1863, Rudolf Virchow, who suggested that lymphoreticular infiltration reflected the origin of cancer at sites of chronic inflammation, identified a connection between inflammation and cancer (16). Subsequently, numerous studies have provided evidence that the host inflammatory responses serve a critical function in various aspects of cancer, including cancer initiation, promotion, progression and metastasis (7,(17)(18)(19) Previously, a number of inflammatory markers have been proposed to have potential for use as predictors of OS and PFS for solid tumors (8,12,(20)(21)(22)(23). The present study identified that NLR, LMR and PLR may be able to predict the prognosis of patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As early as 1863, Rudolf Virchow, who suggested that lymphoreticular infiltration reflected the origin of cancer at sites of chronic inflammation, identified a connection between inflammation and cancer (16). Subsequently, numerous studies have provided evidence that the host inflammatory responses serve a critical function in various aspects of cancer, including cancer initiation, promotion, progression and metastasis (7,(17)(18)(19) Previously, a number of inflammatory markers have been proposed to have potential for use as predictors of OS and PFS for solid tumors (8,12,(20)(21)(22)(23). The present study identified that NLR, LMR and PLR may be able to predict the prognosis of patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…These cell types are able to differentiate into tumor-associated macrophages in tumor tissue, which undergo tumor-promotion and M2-like macrophage polarization and secrete angiogenic factors, including interleukin-8, vascular endothelial growth factor (VGEF) and fibroblast growth factor, then induce further tumor angiogenesis and progression (24,25). Furthermore, monocyte-derived cells may provide nutritional factors that directly promote the growth and survival of malignant tumors (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of CCD cut-off values associated with better survival outcomes have reported inconsistent results. [5,[11][12][13][14][15][16] Some studies have noted superior survival with a CCD > 200 mg/m 2 , but these investigations used heterogeneous modalities of RT, including two-dimensional RT (2D-RT), three-dimensional RT (3D-RT), and IMRT. [5,11,12,14] Lee et al [5] applied NPC-9901 and NPC-9902 trials and found that the locoregional failure-free rate plateaued (88%) after a CCD of 200 mg/m 2 .…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…Ou et al [15] reported significantly higher distant metastasis-free survival (DMFS) and overall survival (OS) rates with CCD ≥ 300 mg/m 2 in concurrent CT, especially for patients with N2-3 lesions. On the other hand, Peng et al [16] reported significantly higher diseasefree survival with CCD ≥ 240 mg/m 2 in concurrent CT.…”
Section: Introductionmentioning
confidence: 96%
“…Several molecular markers have shown values in predicting the survival and DM among NPC patients, yet technical challenges and high costs associated with detecting these markers generally preclude their use in clinic. [ 10 , 12 , 13 ] Although other risk factors also influence survival, [ 3 , 4 , 9 , 14 , 15 ] few studies have assessed the pretreatment baseline parameters to DM. These factors could play a significant role in the choice of treatment NPC patients upon initial diagnosis.…”
Section: Introductionmentioning
confidence: 99%